2014
DOI: 10.1007/s13277-014-2513-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 suppresses the growth and metastasis of HCC cells by targeting E2F3

Abstract: MicroRNAs (miRNAs) function as essential post-transcriptional modulators of gene expression involved in a wide range of physiologic and pathologic states, including cancer. Numerous miRNAs have been deregulated in hepatocellular carcinoma (HCC). Here, we investigated the role of miR-141 in HCC. Decreased expression of miR-141 was observed in both HCC tissues and cell lines. Ectopic overexpression of miR-141 reduced proliferation, migration, and invasion of HCC cells. E2F transcription factor 3 (E2F3) was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 23 publications
(25 reference statements)
4
37
0
Order By: Relevance
“…A number of studies have reported that E2F3 is targeted by various miRNAs and is involved in the genesis and progression of human cancers [31-34]. Our study showed that E2F3 expression was significantly increased by upregulating CRNDE expression, whereas shCRNDE significantly decreased E2F3 expression.…”
Section: Discussionmentioning
confidence: 46%
“…A number of studies have reported that E2F3 is targeted by various miRNAs and is involved in the genesis and progression of human cancers [31-34]. Our study showed that E2F3 expression was significantly increased by upregulating CRNDE expression, whereas shCRNDE significantly decreased E2F3 expression.…”
Section: Discussionmentioning
confidence: 46%
“…MicroRNAs (miRNAs) are small molecules ranging in size from 17 to 22 bases [19][20][21]. miRNA-mediated control is one of the posttranscriptional mechanisms that suppress protein translation by matching to the 3′-untranslated region (UTR, 3′-UTR) of the target gene [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that miR-144 is able to function as a suppressor gene of tumor proliferation and affect the prognosis of patients with osteosarcoma (36,37). Studies have reported that subsequent to transfecting liver cancer HepG2 cells, the plasmids of overexpressed miR-144 are able to promote apoptosis and inhibit the occurrence of liver cancer metastasis by affecting the expression of E2F3 (34,38).…”
Section: Discussionmentioning
confidence: 99%